Comparing the efficacy of two different temperature stimulation in warm acupuncture on acute low back pain: A randomized controlled trial - Tian Li; Siyao Wang; Ke Cheng; Lu Sun; Daopeng Jin; Shen Zhang; Zhen Yang; Zouqin Huang (Integrative Medicine Research)
Background: Warm acupuncture, a combination of the mechanical stimulation of acupuncture and thermal stimulation of moxibustion, is commonly used in treating acute low back pain (LBP). This trial aimed to compare the efficacy of stronger (above 43°C) and weaker (above 40°C) heat stimulation in warm acupuncture on the function and pain in patients with acute LBP due to lumbosacral disc degeneration (LDD). Methods: One hundred and fifty-nine adults were randomly assigned to receive warm acupuncture treatment with silver needle (SvN) or with stainless steel needle (SSN) (1:1). Both groups received a 3-week therapy with 3 sessions per week. The primary outcome was the modified Oswestry Disability Index at week 4. The secondary outcomes included average pain, three physical sign tests and adverse events. Participants were followed up at week 16 and week 28 after randomization. Results: The LBP related disability and pain intensity significantly relieved more in the SvN warm acupuncture group than in the SSN group, in both the short and long term (p<0.001). The between-groups difference in physical signs showed statistical significance only in the short term (p = 0.024), but not in long term (p = 0.081; p = 0.069). Conclusion: Compared with warm acupuncture with stainless-steel needle at above 40°C, warm acupuncture with silver needle at above 43°C relieved more disability and pain in patients with acute LBP due to LDD. Study registration: Chinese Clinical Trial Registry, ChiCTR1800019051.